New binary pulsar constraints on Einstein-æther theory after GW170817. (27th August 2021) - Gupta, Toral; Herrero-Valea, Mario; Blas, Diego; Barausse, Enrico; Cornish, Neil; Yagi, Kent; Yunes, Nicolás
Abstract: The timing of millisecond pulsars has long been used as an exquisitely precise tool for testing the building blocks of general relativity, including the strong equivalence principle and Lorentz symmetry. Observations of binary systems involving at least 1 ms pulsar have been used to place bounds on the parameters of Einstein-æther theory, a gravitational theory that violates Lorentz symmetry at low energies via a preferred and dynamical time threading of the spacetime manifold. However, these studies did not cover the region of parameter space that is still viable after the recent bounds on the speed of gravitational waves from GW170817/GRB170817A. The restricted coverage was due to limitations in the methods used to compute the pulsar 'sensitivities', which parameterize violations of the strong-equivalence principle in these systems. We extend here the calculation of pulsar sensitivities to the parameter space of Einstein-æther theory that remains viable after GW170817/GRB170817A. We show that observations of the damping of the period of quasi-circular binary pulsars and of the triple system PSR J0337+1715 further constrain the viable parameter space by about an order of magnitude over previous constraints.